Hypotheses and evidence related to intense sweeteners and effects on appetite and body weight changes: A scoping review of reviews. - Annhild Mosdøl; Gunn Elisabeth Vist; Camilla Svendsen; Hubert Dirven; Inger Therese Laugsand Lillegaard; Gro Haarklou Mathisen; Trine Husøy (PLoS ONE)
Observed associations between consumption of diet foods and obesity have sparked controversy over whether intense sweeteners may promote weight gain, despite their negligible energy contribution. We conducted a scoping review of reviews, to obtain an overview of hypotheses, research approaches and features of the evidence on intense sweeteners' potential relationships to appetite and weight changes. We searched for reviews of the scientific literature published from 2006 to May 2017. Two reviewers independently assessed title and abstracts, and full text publications. Arksey and O'Malley's framework for scoping reviews guided the process. We extracted and charted data on characteristics of the reviews and the evidence presented. The 40 included reviews present hypotheses both on how intense sweeteners can reduce or maintain body weight and on how these can promote weight gain. We classified only five publications as systematic reviews; another nine presented some systematic approaches, while 26 reviews did not describe criteria for selecting or assessing the primary studies. Evidence was often presented for intense sweeteners as a group or unspecified, and against several comparators (e.g. sugar, water, placebo, intake levels) with limited discussion on the interpretation of different combinations. Apart from the observational studies, the presented primary evidence in humans is dominated by small studies with short follow-up-considered insufficient to assess weight change. Systematic reviews of animal studies are lacking in this topic area. The systematic evidence only partly explore forwarded hypotheses found in the literature. Primary studies in humans seem to be available for systematic exploration of some hypotheses, but long-term experimental studies in humans appear sparse. With few exceptions, the reviews on intense sweeteners and weight change underuse systematic methodology, and thus, the available evidence. Further studies and systematic reviews should be explicit about the hypothesis explored and elucidate possible underlying mechanisms.